Organizational Culture and Work-life Balance : The Secret to Boosting Employee Performance - Salsabila Dwinoor Virgi Karlisa; Agus Frianto (Universitas Negeri Surabaya, 2026)
As one of the most stable companies in providing transportation and freight forwarding services, supported by effective human resource management, issues related to employee performance are inevitable within the organization. This study aims to examine the influence of organizational culture and work-life balance on employee performance. A quantitative method was employed, involving 46 respondents as the research sample. The results indicate that organizational culture has a significant positive effect on employee performance, and work-life balance also has a significant positive effect on employee performance. Furthermore, the findings reveal that organizational culture and work-life balance jointly have a significant positive influence on employee performance. The implication of this study shows that the company needs to strengthen the implementation of organizational culture, especially in the aspects of work philosophy and performance-based reward system, and review the workload balance to improve employees' social life outside work. This effort is important to create an adaptive and balanced work environment and encourage overall improved employee performance. Future research is encouraged to use a larger and more diverse sample across different service industries, such as banking, tourism, and education, to gain broader insights into the influence of 0rganizational culture and work-life balance on employee performance.